(3GdeGdjI GdYGeI (B/ s - (3Hf GdYGeQ, fYjeIs; (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs ((3GdLRGFQs (3LGeYI GdLRGFQ(B3: (3cdjI GdYdhe GdEbJUGOjI, GdYdhe GdJLGQjI hYdhe GdJSjjQs, 2015)
(3GdSjGSI GdeGdjI, eaghe GdeGdjI GdYGeI, bhGYO heHGOF GYOGO GdejRGfjI GdYGeI, GdfabGJ GdYGeI, eQGbHI GdeGdjI GdYGeI, GdGjQGOGJ GdYGeI, eONd ddfXQjI GdYGeI ddVQjHI, bhGfjf GdeGdjI, JfajP ejRGfjI GdOhdI, eQGbHI GdeGdjI GdYGeIs
(3eQGLY U(B.101s
Keywords: (3GdGjQGOGJ hGdfabGJs; (3GdSjGSI GdeGdjIs; (3GdeGdjI GdYGeIs